Students' metacognition in solving non-routine problems - Kholid, Muhammad Noor; Ahadiyati, Arina (Al-Jabar: Jurnal Pendidikan Matematika, 2022)
Students’ metacognition abilities based on their aspects have different levels. Metacognition aspects had categorized into parts of awareness aspects, evaluation aspects, and aspects of regulation. This study aims to describe how students are metacognitive in solving non-routine problems based on awareness, evaluation, and regulation characteristics. This research is a descriptive qualitative study with a sampled class VIII A Junior High School Batik Special Program (PK) Surakarta, which consisted of six students. The instruments in this research are non-routine problems or tests, observation sheets, and interview guidelines. The questions validator in this research are two teachers and a Mathematics Education lecturer from the University of Muhammadiyah Surakarta. The data collection technique uses tests, observations, and interviews. The data analysis technique of research had carried out through three stages: data reduction, data presentation, and conclusion drawing. This study concluded that the student's metacognition of eighth grade in solving non-routine problems had not developed better. Only one student can ideally find the metacognition aspects of awareness, evaluation, and regulation. Compared to medium-capable students, students with high abilities can discover the metacognition aspects well. In comparison, students with low skills have not been able to find all indicators of metacognition. Based on the results, further research may discover students’ obstacles in implementing metacognition for mathematical problem-solving.